Association of a complement receptor 1 gene variant with baseline erythrocyte sedimentation rate levels in patients starting anti-TNF therapy in a UK rheumatoid arthritis cohort: results from the Biologics in Rheumatoid Arthritis Genetics and Genomics Study Syndicate cohort. - Bluett, J; Ibrahim, I; Plant, D; Hyrich, K; Morgan, A; Wilson, A; Isaacs, J; Barton, A (2014)
Eligibility for anti-tumour necrosis factor (TNF) therapy in most European countries is restricted to severe, active rheumatoid arthritis (RA). The DAS28 score is a marker of disease severity and incorporates one of two inflammatory markers, erythrocyte sedimentation rate (ESR) or C-reactive protein. We aimed to determine the relation between genetic variants known to affect ESR and levels of ESR in patients with active RA. DNA samples were genotyped for four single-nucleotide polymorphisms (SNPs) rs7527798 (CR1L), rs6691117 (CR1), rs10903129 (TMEM57) and rs1043879 (C1orf63). The association between SNPs and baseline ESR, baseline DAS28-ESR, and change in DAS28-ESR was evaluated. Baseline ESR was significantly associated with CR1 rs6691117 genotype (P=0.01). No correlation was identified between baseline DAS28-ESR or change in DAS28-ESR. In conclusion, genetic variation in the gene encoding CR1 may alter ESR levels but not DAS28-ESR, indicating no adjustment for CR1 genotype is required in the assessment of patients with severe active RA.